Research progress on sources and inhibition measures of acrylamide in fermented food - SHANG Yuhao, ZHU Xiajian, TIAN Dongwei, CHENG Pingyan, HU Jianfeng, WANG Diqiang (Zhongguo niangzao)
Fermented food is favored by consumers for its unique technology and flavor. However, harmful substances such as acrylamide are produced in the fermentation process along with the Maillard reaction, which has adverse effects on consumers' health. The formation mechanism of acrylamide in food was introduced, the formation mechanism and source of acrylamide in fermented food (fermented condiments, fermented dairy products, fermented meat products and other fermented products) were summarized, and the control method of acrylamide of fermented food in the process was proposed.